Measurement of in vivo cerebral volumetric strain induced by the Valsalva maneuver - Mousavi, Seyed Reza; Fehlner, Andreas; Streitberger, Kaspar-Josche; Braun, Juergen; Samani, Abbas; Sack, Ingolf (Journal of Biomechanics, 2014)
Compressibility of biological tissues such as brain parenchyma is related to its poroelastic nature characterized by the geometry and pressure of vasculature and interconnected fluid-filled spaces. Thus, cerebral volumetric strain may be sensitive to intracranial pressure which can be altered under physiological conditions. So far volumetric strain has attained little attention in studies of the mechanical behavior of the brain.This paper reports a study of measuring the in vivo cerebral volumetric strain induced by the Valsalva maneuver (VM) where forced expiration against a closed glottis leads to a transient increase in the intracranial pressure. For this purpose we applied three-dimensional magnetic resonance imaging equipped with a patient-controlled acquisition system to five healthy volunteers. With each volunteer, three experiments were performed: one with VM and two in resting state. i.e. normal ventilation, which were conducted before and after VM. The VM data were registered to reference data by morphology based non-rigid deformation, yielding 3D maps of total displacements and volumetric strain. On average, VM induced volumetric strain correlated to whole-brain dilatation of -3.14±0.87% and -2.80±0.71% compared to the reference states before and after VM, respectively. These values were well reproduced by repetitive experiments during the same scan as well as by repeated measurements in one volunteer on different days. Combined with literature data of intracranial pressure changes, our volumetric strain values can be used to elucidate the static compression modulus of the in vivo human brain. These results add knowledge to the understanding of the brain's biomechanical properties under physiological conditions. © 2014 Elsevier Ltd.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Brain tissue; Compression modulus; Dilatation; Elastography; Intracranial pressure; MRE; Poroelasticity; Valsalva maneuver; Volumetric deformation